2019
DOI: 10.1002/jcop.22262
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and depression among Chinese drug users: Mediating effect of resilience and moderating effect of gender

Abstract: This study aims to explore potential correlations between gender, loneliness, resilience, and depression simultaneously among Chinese drug users; and especially to investigate the mediating effect of resilience and the moderating effect of gender on the correlation between loneliness and depression. Participants of this study included 513 drug users (399 men and 114 women) who were under treatment in two compulsory drug treatment institutions in one Eastern Chinese city. All participants completed the UCLA (Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…These results then explain that resilience has the potential to reduce levels of loneliness and subsequently reduce depression. It is because resilience is the ability that a person has to deal with various problems, and this resilience can be seen through the attitude shown when a person adapts and finds solutions to the problems faced (Cao & Liu, 2020;Zhao et al, 2018). In everyday life, someone with good resilience will show attitudes based on seven important aspects, such as emotion regulation, related to one's ability to control one's emotions and act positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results then explain that resilience has the potential to reduce levels of loneliness and subsequently reduce depression. It is because resilience is the ability that a person has to deal with various problems, and this resilience can be seen through the attitude shown when a person adapts and finds solutions to the problems faced (Cao & Liu, 2020;Zhao et al, 2018). In everyday life, someone with good resilience will show attitudes based on seven important aspects, such as emotion regulation, related to one's ability to control one's emotions and act positively.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with good resilience can adapt their body, mind, and spirit to current life circumstances, so the higher their resilience, the lower the loneliness felt (Rachmawati et al, 2019;Ramadanti & Herdi, 2022). Loneliness and depression can be mediated by resilience because, in everyday life, resilience can overcome various difficulties, tragedies, and other negative events, so that the individual can reduce the possibility of mental health problems (Cao & Liu, 2020;Zhao et al, 2018). In addition, maximizing resilience can reduce loneliness and facilitate the recruitment of the emotional and psychological resources needed to manage aspects of life that can lead to depressive symptoms (Chasanah & Wijaya, 2023;Rohmadani & Winarsih, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in the levels and rates of loneliness have not been observed consistently, but there is some suggestion that loneliness may be more prevalent among older women because they tend to outlive their partners (Vozikaki et al, 2018 ). Although some studies have found no gender differences in the link between loneliness and inflammation (Steptoe et al, 2004 ; Mezuk et al, 2016 ), a recent meta-analysis (Maes et al, 2019 ) suggests that loneliness may be associated with worse health-related outcomes for women relative to men (Steptoe et al, 2004 ; Thurston and Kubzansky, 2009 ; Cao and Liu, 2020 ). Further, there are strong links between gender and inflammation, with women tending to have higher levels of circulating inflammatory markers, such as CRP (Darnall and Suarez, 2009 ; O'Connor et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%